Syphilis in the practice of doctors of related specialties - Anna L. Evseeva; Vera V. Ryabova; Sergei V. Koshkin; Olga S. Kovrova (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
The article presents clinical cases of syphilitic infection from our own practice, which were not recognized by doctors of related specialties at the early stages of the development of the disease. In the first observation, the manifestations of syphilis were regarded as a surgical pathology in the patient, which entailed surgical intervention, which was not necessary as such. The following clinical case demonstrates lesions of the mucous membranes in syphilis, mistakenly recognized by the therapist as streptococcal angina. The atypical hard chancre in the final observation disorientated the surgeon, that led to a delay in the correct diagnosis and, accordingly, in the appointment of adequate treatment. Regardless of the specialty, everyone should not forget about the variety of manifestations of syphilis in all periods. The lack of alertness among doctors of related specialties contributed to the delayed diagnosis and the appointment of specific anti-syphilitic therapy.